EFEKTIVITAS KEPEMIMPINAN DALAM RANGKA MENINGKATKAN KOMITMEN ORGANISASI DI PT BIRO KLASIFIKASI INDONESIA (PERSERO) - Dina Purnama Sari (Cakrawala - Jurnal Humaniora, 2010)
The objectives of this research is to describe the roles of leadership effectiveness in increasing organizational commitment at PT Biro Klasifikasi Indonesia (Persero). The method of this research is descriptive quantitative and the instrument for collecting data is questionnaires. The main object of this research is Director of Research & Development Department. The respondents are 30 employees in Research & Development Department, which collaboration with Personel & General Affair Division, Planning Department, Finance Department, and Survey Division. The research result shows: 1) the role of leadership effectiveness in increasing of organizational commitment is high (mean 100, 93), 2) organizational commitment is high (mean 102,23), and 3) there is positive correlation between leadership effectiveness and organizational commitment.The conclusion is that leadership effectiveness has significantly increased organizational commitment. It is because there is strong intention or desire to achieve organization’s objectives under the supervision of effective leader. Keywords: leadership effectiveness, organizational commitment